The formation of the property of religious organizations in post-Soviet states - Hasanov, Simran S. (Opción, 2019)
This article considers the peculiarities of formation of the property of religious organizations in post-Soviet States through institutional method to determine the location of the property of religious communities. As a result, it is possible to promote the redistribution of population between densely populated and sparsely populated areas, stimulating the development of religious organizations in the less popular areas. In conclusion, the obtained data contributed to the formation of recommendations for improving the legislation of the countries of Commonwealth of Independent States that an effective mechanism for the formation of the right of ownership of religious organizations will be established.